Kegiatan mahasisawa Universitas Muhammadiyah Purwokerto peserta kkn terpadu di perpustakaan sekolah di wilayah kabupaten Banyumas - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT This research is aimed to find out the k/nds of snaients' contribution at some schools' libraries. This research was done Public Service Unit of Muhammad&li University film March May 2007. The method used in this research is In analysing the documents u the fin,,i report of Public Field Work. Based on the result. of the research, it can be concluded Out the students' contributions can be both technical and financial aids. The technical aids, such as.- room )nanagenient, inventarization, cia5sification, catalogue, making book card, making member card, putting the book label, giving the book cover, putting the data in computer, book shelling, arranging the wall paper an doing the administration as well as circulation service. The _financial aid Wa,S Rp. 3.134,850 used iu buy the libraries' needs, including books, bookselres, paint and writing utensils. Key words